The Effect of Bouncing Ball Practice on The Volleyball Forepass Ability of Extracurricular Students Smp Negeri 1 Pasemah Air Muruh - Alparizi, Iksan; Pujianto, Dian; Rizky, Oddie Barnanda; Nurkadri; Julhi, Abang Ismail Bin Haji Abang (Indonesian Journal of Sport, Health and Physical Education Science, 2025)
This study seeks to assess how the bouncing ball training approach affects the bottom passing skills of students engaged in volleyball extracurricular activities at junior high school state 1 Pasemah Air Keruh. The research design follows a one-group pretest-posttest format, which does not involve a comparison group. The participants of this study comprised all students who actively chose to engage in this research until its conclusion, with a total of 16 children involved in volleyball extracurricular activities. The tools for this study consisted of tests and assessments based on the Brady method. The findings indicated that the bouncing ball training method positively influenced down-passing skills. When testing the hypothesis, the computed t value was 12.5, which exceeds the t table value of 1.746. This result leads to the rejection of the null hypothesis and the acceptance of the alternative hypothesis, signifying a notable advancement in bottom passing ability as a result of the bouncing ball training method.